Using Gramsci : a new approach - Filippini, Michele (Reading Gramsci., 2017)
This is a new approach to one of the greatest political theorists, Antonio Gramsci. Gramsci's Prison Notebooks are one of the most popular Marxist texts available and continue to inspire readers across the world. Here, Michele Filippini proposes a new approach based on the analysis of previously ignored concepts in his works, creating a book which stands apart. Including chapters on ideology, the individual, collective organisms, society, crisis and temporality, Using Gramsci offers a new pattern in Gramscian studies aimed to speak to the broader audience of social sciences scholars beyond the field of political theory and Marxism, while remaining firmly rooted in his writings. Working from the original Italian texts, Filippini also examines the more traditional areas of Gramsci's thought, including hegemony, organic intellectuals and civil society. This book will be perfect for all scholars and students of Gramsci's thought.